Effect of BAP (6-Benzyl Amino Purine) and NAA (Naphtalen Acetic Acid) on the Induction of Axillary Shoots in Sandalwood (Santalum album L.) - Imaniah Bazlina Wardani (META: Journal of Science and Technological Education, 2022)
Sandalwood (Santalum album L.) is a native species of East Nusa Tenggara that is facing a population reduction in its natural environment as a result of exploitation. In a relatively short amount of time, a large quantity of seeds is required. One of the methods used is vegetative propagation through tissue culture techniques. The inclusion of growth regulators such as BAP and NAA to the culture medium is crucial to the successful induction of shoots via tissue culture. This study's objective was to examine the influence of BAP and NAA on the induction of axillary shoots in Sandalwood (Santalum album L.). Using a completely random design with a factorial pattern consisting of 16 treatments and 3 replications, the study used a design that was fully randomized. The first component was BAP concentrations (0 mg/l, 0.5 mg/l, 1 mg/l, and 2 mg/l), while the second factor was NAA concentrations (0 mg/l, 0.1 mg/l, 0.25 mg/l). l and 0.5 mg/l). The findings of the research demonstrated that the addition of BAP and NAA affected the day of emergence of axillary shoots, the number of axillary shoots, the average length of the shoots, and the number of leaves. The most efficient combination of concentrations for generating axillary shoots in Sandalwood (Santalum album L.) was BAP 2 + NAA 0 mg/l.